PENGOLAHAN LIMBAH CAIR INDUSTRI PERCETAKAN SECARA ELEKTROLISIS DENGAN ELEKTRODA KARBON/KARBON - Wiskandini, Yunaska (Chem Info Journal, 2013)
Offset industry potentially produces liquid waste that can pollute the environment. Generally, liquid industrial waste due to leaching of printing plates and film printing equipment like ink, turpentine, gasoline, and detergents. Offset industry wastewater contains many organic chemicals that are difficult to be degraded directly by environment such as alcohol, benzene, and contain heavy metal such as manganese. This research use electrolysis method with carbon as electrodes, Na2SO4 as the supporting electrolyte, H2SO4 and NaOH as adjuster to pH condition of the sample, to improve the quality of printing waste solution on the parameters were type, spacing and size of electrode and sample volume of wastewater, variated parameters were application potential, pH of the sample and electrolysis time. Analysis of the sample after electrolysis using Pelkin Elmer 1300 AAS, UV-Vis Spectrophotometer 1601, and Turbidity unit HAC 2100P. Electrolysis with application potential of 5 volts, pH 4 and electrolysis time 150 minutes resulted in COD, turbidity, and Mn values decreasing up to 91.08%, 99.40%, 97.85%, respectively. This result showed that electrolysis method can be applied to treat offset industry.